Pengaruh Corporate Social Responsibility dan Profitabilitas terhadap Harga Saham Perusahaan Batubara yang Terdaftar di BEI Periode 2020-2024 - Gunawan, Fauziah Nadya Alfreda; Irawan, Arry; Kusumastuti, Endah Dwi; Ramadhani, Annas Rahmat (Indonesian Accounting Literacy Journal, 2026)
This study discusses the effect of CSR and profitability on the stock prices of coal companies on the IDX for the period 2020–2024. The issue raised is the increasing attention to the environmental impact of mining activities and how companies respond to it through sustainability disclosure. The purpose of the study is to analyze the relationship between CSR, profitability, and stock prices in sectors that have high environmental risks. The method used is a quantitative approach with secondary data from annual and sustainability reports, as well as logistic regression analysis using Eviews. The sample was determined through purposive sampling and produced 35 sample data. The results of the study show that CSR has a negative insignificant effect, profitability has a positive significant effect, and both have a simultaneous effect on stock prices, indicating that investors continue to consider aspects of sustainability and financial performance, especially in sectors with large environmental impacts.